Motor Complications of Dopaminergic Medications in Parkinson's Disease - Freitas, Maria Eliza; Hess, Christopher W.; Fox, Susan H. (Seminars in Neurology, 2017)
Motor complications are a consequence of the chronic treatment of Parkinson's disease (PD) and include motor fluctuations (wearing-off phenomenon) and levodopa-induced dyskinesia. Both can have a significant impact on functionality and quality of life; thus, proper recognition and management is essential. The phenomenology and temporal relationship of motor complications to the schedule of levodopa dosing can be helpful in characterizing them. There are several therapeutic approaches to motor complications, including pharmacological and surgical options. The authors summarize the different types of motor complications according to phenomenology and the currently available medical treatments, including ongoing trials for the management of this condition.
Keywords: motor fluctuations; motor complications; levodopa-induced dyskinesia; Parkinson's disease